Synthesis and Evaluation of New Heteroaryl Nitrones with Spin Trap Properties - Aliaga-Vidal, C; Aliaga-Vidal, C (Royal Society of Chemistry, 2020)
A new series of heteroaryl nitrones were synthesized and evaluated as free radical traps due to the results showed in our previous report. The physicochemical characterization of these new nitrones by electron spin resonance (ESR) demonstrated their high capability to trap and stabilize different atom centered free radicals generated by the Fenton reaction. Additionally, we intensely studied them in terms of their physicochemical properties. Kinetic studies, including the use of a method based on competition and the hydroxyl adduct decay, gave the corresponding rate constants and half-lives at the physiological pH of these newly synthesized nitrones. New nitrones derived from quinoxaline 1,4-dioxide heterocycles were more suitable than DMPO to trap hydroxyl free radicals with a half-life longer than two hours. We explain some of the results using computational chemistry through density functional theory (DFT). © 2020 The Royal Society of Chemistry.